Development of injectable high molecular weight hyaluronic acid hydrogels for cartilage regeneration. Issue 8 (2nd August 2016) - Mondal, Shraddha; Haridas, Neena; Letha, S. Sneha; Vijith, V.; Rajmohan, G.; Rosemary, M. J.
ABSTRACT: The study focuses on developing hyaluronic acid (1200 kilo Dalton) hydrogels for cartilage regeneration. In spite of being highly biocompatible; a large amount of water absorption and easily degrading nature restricts the use of hyaluronic acid in the field of tissue regeneration. This can be rectified by crosslinking hyaluronic acid with a crosslinking agent such as divinyl sulfone; which results in a biocompatible hydrogel with superior rheological properties. Different amounts of divinyl sulfone have been used for crosslinking hyaluronic acid to get three types of hydrogels with differing properties. Swelling studies, rheology analysis, enzymatic degradation and scanning electron microscopic analysis were conducted on all the different types of hydrogels prepared. Viscoelastic properties of the hydrogel were analyzed so that a hydrogel with better elastic property and stability is obtained. Scanning electron microscopy was used to study the morphology of the HA hydrogels. The cytotoxicity testing was conducted to prove the non-toxic nature of the hydrogels and cell culture studies using adipose mesenchymal stem cells showed better adhesion and proliferation properties in all the three hydrogels. Thus hyaluronic acid hydrogel makes a promising material for cartilage regeneration.